Analysis of digital tools and mobile apps for creating CV - Tkachuk, Yu. M. (My University, 2021)
Nowadays competition on the labor market is growing. It is getting harder to get the job. One of main points that employers observe is the candidate’s CV. It is the first thing that they know about you. It helps to systematize the information about the employee. So it is very important to have successful professional resume. Some people may have difficulties with writing it, but in the era of digital technologies there are many opportunities to make life easier, in particular, to simplify the process of creating CV. There are plenty of websites and mobile apps that offer to create CV online.
Keywords: websites; mobile applications; online services; create CV; job; job market